Raising Steam [compact disc, unabridged] : a Discworld novel - Pratchett, Terry (Pratchett, Terry. Discworld series (New York, N.Y.), 2014)
Change is afoot in Ankh-Morpork - Discworld's first steam engine has arrived, and once again Moist von Lipwig finds himself with a new and challenging job.